The Spokesman, Oct 9, 1990, Vol. 2, No. 2 - The Editorial Team (Morgan State University, 1990)
Homecoming Events: The annual Homecoming celebrations included various activities such as a football game, parade, step shows, and a concert featuring popular hip-hop artists like Queen Latifah, Poor Righteous Teachers, YZ, Kool G, Rap, and D.J. Polo. The theme was "The Power of Our Heritage"​(The Spokesman, Oct 20, …)​​(The Spokesman, Oct 20, …)​. Campus Security and Safety: There were discussions on improving campus security following incidents at campus events. Plans included hiring new campus police officers and discontinuing the contract with STOP security​(The Spokesman, Oct 20, …)​​(The Spokesman, Nov 9, 1…)​. Student Activities: The calendar section lists various student activities, including lectures, tutoring sessions, organizational meetings, and social events such as parties, fashion shows, and comedy nights. These activities aim to engage and support students throughout the month​(The Spokesman, Oct 20, …)​. Superstition and Real-life Experiences: An article discusses the actor Danny Glover and his connection to the film "To Sleep with Anger," where he explores the themes of superstition and family legacy through his personal experiences​(The Spokesman, Oct 20, …)​​(The Spokesman, Oct 20, …)​. Editorial and Opinion Pieces: The editorial section addresses student participation and the importance of being active in the Student Government Association. It highlights the lack of motivation among students to engage in governance and community activities, emphasizing the need for collective effort and involvement
Keywords: Editorials and Opinions, Editor’s Comments; Musicians and Entertainers; Student extracurricular activities and cultural events; Homecoming; Campus Safety and Crime